2016
DOI: 10.17229/jdit.2016-0905-023
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal scintigraphy in the supine lateral head position

Abstract: The examination with lacrimal scintigraphy showed that the supine side-down eye position of the test subject inhibited the transfer of the tracer into the lacrimal sac. The result means that utilizing gravitation offers the patient a convenient alternative to prolong the ocular contact time of each eye drop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The next article on 'Lacrimal scintigraphy in the supine lateral head position', by Pohjanpelto et al [3]. The authors investigated lacrimal scintigraphy and showed that the supine side-down eye position of a test subject is inhibited by the transfer of the tracer into the lacrimal sac.…”
Section: Editorial Review Editorial Review 2016 -Nuclear Medicine DImentioning
confidence: 99%
“…The next article on 'Lacrimal scintigraphy in the supine lateral head position', by Pohjanpelto et al [3]. The authors investigated lacrimal scintigraphy and showed that the supine side-down eye position of a test subject is inhibited by the transfer of the tracer into the lacrimal sac.…”
Section: Editorial Review Editorial Review 2016 -Nuclear Medicine DImentioning
confidence: 99%